EFEK NITROCARBURIZING PADA MATERIAL LOW CARBON STEEL TERHADAP KETAHANAN KOROSI DAN KEKERASAN - Al Afghani, Fajar; Hermawan, Erwan; Shaleha, Siti (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
The use of steel is currently experiencing a fairly rapid growth. Low carbon steel is widely used in radiometallurgical installation, especially for structural components of conveyors, chains, gears and so on. Its use is increasingly massive so that various kinds of developments in steel materials have been carried out. One of them is to improve the quality of steel, so it can be used for a long time. One method that can be used to improve the quality of steel is nitrocarburizing process. This research focused on the effect of the nitrocarburizing process on corrosion rate. The nitrocarburizing process was carried out on several samples with different temperatures but the same gas. Increasing the temperature in the nitrocarburizing process resulted in harder specimen surface. The increase in hardness was obtained based on the temperature difference which increased from 192 HV for the sample before dinitrocarburizing to 793 HV for the 450 ºC nitrocaburizing sample. In addition, corrosion resistance increases with increasing nitrocarburizing temperature. The nitrocarburizing process causes the diffusion of C and N atoms to form a compound layer, diffusion layer, and transition layer consisting of a layer of ε-Fe2-3N, γ’- Fe4N, Fe2(N, C)1-z, making the surface layer of the material become hard and resistant to corrosion.